Monitoring particle trajectories for wave function parameter aquisition in quantum edge computation. Issue 1 (1st January 2021) - Itami, Teturo; Matsui, Nobuyuki; Isokawa, Teijiro; Kouda, Noriaki; Hashimoto, Takanori
Abstract : Artificial intelligence(AI) technology expected as a robot brain is advancing day by day. However, computers are insufficient to drive AI without the dramatic development of their processing power. On the other hand, the development of quantum computers is progressing to break the barrier of classical computers. Moreover, there has been an argument that quantum mechanics is one of the leading ideas to explain human mental power and such an argument has become active recently. But unfortunately we cannot mount the quantum processor on the robot brain as its edge computer. This is because large-scale equipments that guarantee ultra-low temperature are required to maintain superposition, which is a key point of quantum computers. In this paper, we show a method of performing quantum computation with a classical mechanical device. We found that wave function parameters can be determined by monitoring particles trajectories under quantum fluctuations. We take up Deutsch's coin authenticity decision problem. We emphasize that it can be developed as hardware, not just an algorithm.